A More Complex Relationship Between GDP Growth Rate and the Luxury Goods Market - Zhu Yue (SHS Web of Conferences)
Numerous literatures have shown a strong correlation between GDP growth and luxury goods, but the data in this study show something subtly different. This study collected the relationship between GDP growth rate and luxury consumption in Japan, the Asia-Pacific region (excluding Japan), Europe and North America, and focused on the total marketing volume of LVMH and Hermes for regression between the two brands. The regression results show that the GDP growth rate has no significant impact on luxury sales, which is different from the traditional economic theory. On this basis, the study attempts to explore the reasons why there is no significant relationship between the two. The research emphasizes that consumer psychology, social stratification, regional policy differences and other reasons will have an important impact on the luxury market. This suggests that relying on GDP growth alone as a predictor of luxury sales may not be enough. Need a more comprehensive approach to analyze the relationship between the two, including social distribution, macroeconomic environment, cultural factors and so on. This study contributes to the existing literature by providing an insignificant relationship between macroeconomic conditions and luxury consumption, providing valuable implications for brand managers, investors, and policy makers.